Emerging Safety of Intramedullary Transplantation of Human Neural Stem Cells in Chronic Cervical and Thoracic Spinal Cord Injury. Issue 4 (24th May 2017) - Levi, Allan D; Okonkwo, David O; Park, Paul; Jenkins, Arthur L; Kurpad, Shekar N; Parr, Ann M; Ganju, Aruna; Aarabi, Bizhan; Kim, Dong; Casha, Steven; Fehlings, Michael G; Harrop, James S; et al.
Abstract: BACKGROUND: Human central nervous system stem cells (HuCNS-SC) are multipotent adult stem cells with successful engraftment, migration, and region-appropriate differentiation after spinal cord injury (SCI). OBJECTIVE: To present data on the surgical safety profile and feasibility of multiple intramedullary perilesional injections of HuCNS-SC after SCI. METHODS: Intramedullary free-hand (manual) transplantation of HuCNS-SC cells was performed in subjects with thoracic (n = 12) and cervical (n = 17) complete and sensory incomplete chronic traumatic SCI. RESULTS: Intramedullary stem cell transplantation needle times in the thoracic cohort (20 M HuCNS-SC) were 19:30 min and total injection time was 42:15 min. The cervical cohort I (n = 6), demonstrated that escalating doses of HuCNS-SC up to 40 M range were well tolerated. In cohort II (40 M, n = 11), the intramedullary stem cell transplantation needle times and total injection time was 26:05 ± 1:08 and 58:14 ± 4:06 min, respectively. In the first year after injection, there were 4 serious adverse events in 4 of the 12 thoracic subjects and 15 serious adverse events in 9 of the 17 cervical patients. No safety concerns were considered related to the cells or the manual intramedullary injection. Cervical magnetic resonance images demonstrated mild increased T2 signal change in 8 of 17 transplanted subjects without motor decrements or emerging neuropathic pain. All T2 signal change resolved by 6 to 12 mo post-transplant. CONCLUSION: A total cell dose of 20 M cells via 4 and up to 40 M cells via 8 perilesional intramedullary injections after thoracic and cervical SCI respectively proved safe and feasible using a manual injection technique.